Contributions of Jean Watson's theory to holistic critical thinking of nurses - Fernando Riegel; Maria da Graça Oliveira Crossetti; Diego Silveira Siqueira
ABSTRACT Objective: to reflect on the contributions of Jean Watson's theory to the nurses' holistic critical thinking. Method: This is a theoretical reflection article, on which scientific productions about Jean Watson's human care theory, published in national and international periodicals, were based. Results: Jean Watson's theory and its contribution to the nurses' holistic critical thinking; the interface of critical holistic thinking in teaching the nursing diagnosis process according to Watson's theory; contributions of critical holistic thinking to the nursing field. Final considerations: Jean Watson's theory is based on the humanistic aspects and on the ethical and spiritual dimensions of care, considering the characteristics of each individual and their bio-psycho-spiritual-social needs, which can contribute fundamentally to the development of holistic critical thinking and to the role of the nurse in care, teaching and research fields